مدى تطبيق جودة الخدمات المكتبية في جامعة تشرين من وجهة نظر طلبتها - حنا فاضل; غفر غيداء (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى التعرف إلى أهمية مؤشرات جودة الخدمات المكتبية ومدى تطبيقها في جامعة تشرين من وجهة نظر طلبتها، وكذلك التعرف إلى الفروق في وجهة نظر طلبة جامعة تشرين تبعاً لمتغيري (الكلية، والصف الدراسي). استخدم البحث المنهج الوصفي التحليلي، واشتملت العينة على (480) طالباً وطالبة من طلبة جامعة تشرين للعام الدراسي 2009/2010. ولتحقيق هدف البحث صممت استبانة احتوت (32) فقرة، افترض أنها مؤشرات الجودة في الخدمة المكتبية. أظهرت النتائج أن (54.37%) من أفراد العينة وافقوا على أن جودة المؤشرات المذكورة في الإستبانة مهمة جداً، مقابل (35.23%) مهمة إلى حد ما، في حين أن (10.43%) لم يوافقوا على أهمية هذه المؤشرات. ورأى (16%) من أفراد العينة أن المؤشرات المذكورة متوافرة بدرجة عالية في جامعة تشرين، مقابل (40.24%) رأوا أنها متوافرة بدرجة متوسطة، و(43.78%) رأوا أنها متوافرة بدرجة ضعيفة. كما أظهرت النتائج وجود فروق دالة بين الطلبة الجامعيين وطلبة الدراسات العليا، وبين الكليات. قدم البحث مقترحات منها تطبيق الجودة في الجامعات السورية، وإجراء مزيد من البحوث. The purpose of the research is to study the attitudesof Tishreen University students in indicators of Library Service Quality, and the extent of its application in the University, and to study the difference of such attitudes according to the two variablesof faculty and study class. The research used adescriptive analytic research approach, and the sample included (480) studentsofTishreen University for the academic year 2009/2010. To achieve the objective of the research, aquestionnaire has included (32) items,which were supposed to be indicatorsof Service Quality. The final results showed that (54.37%) of the examined sample approved thatService Qualityindicators mentioned in thequestionnaire are very important, (35.23%) nearly approved that theseindicators are somehow important, and (10.43%) did not approve that they are important at all. The results indicated that (16%) of the sample found that these indicators are there at a high levelin Tishreen University, where (40.24%) found that they arethere at amediumlevel, and (43.78%) found that they arethereatlowlevel. In fact, there are differences between the undergraduate students and postgraduate students; also there are differences between faculties’ students. The Research has finally presented suggestions concerning thequalityapplication among the Syrian universities, as well as carrying further research on them.